Analysis of adverse drug reactions of antimicrobial agents reported to ADR monitoring centre of a rural tertiary care teaching hospital - Nagaiah, Bhaskar H.; Patil, Shivaraj Basavaraj; Vahila, Nallavelly; Venkata Rao, Y.; Raikar, Shrinivas R.; Sajid, Mohd (International Journal of Basic & Clinical Pharmacology, 2017)
Background: ADRs are iatrogenic diseases, escalates the burden of health care system by increasing the morbidity and mortality and also additional cost of ADRs management to patients. Methods: A prospective observational study was conducted over 1 year from January 2015 to December 2015. The yellow forms dropped in the red ADR boxes are collected and ADRs due to antimicrobials were analyzed for demographic data, causality, severity, drugs implicated, and organ system affected. The data were presented as counts and percentages. Results: Cephalosporins were the most common antimicrobial class implicated in ADRs, and the dermatological system was the most common system affected by ADRs. All the reactions either belonged to the probable or possible category. Majority of reactions were non-serious. Conclusions: Regular prescription auditing and awareness about polypharmacy will further reduce ADRs due to antimicrobials.